ENVIRONMENTAL CIVIL RESISTANCE IN LEMBAK ETHNIC FOLK STORIES AND ITS IMPLEMENTATION IN LITERATURE LEARNING IN JUNIOR HIGH SCHOOL - Nugroho, Agung (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2025)
The purpose of this study is to describe environmental civilization in Lembak ethnic folklore and its implementation in literature learning in junior high schools. The research method used is a qualitative descriptive method with a library approach. Data sources are folklore and student learning outcomes. The data in this study are quotes that show environmental civilization encompassing; environmental civilization, ecosystem civilization, population civilization in Lembak ethnic folklore. Based on the results of the study, it is known that environmental civilization is a scope occupied by a living creature together with living and non-living things. Not only that, there is also a complex system, consisting of various elements that interact with each other, including humans and other living things, and also includes components of space, objects, power, and conditions that affect life and development between living things. In ecosystem civilization refers to the reciprocal relationship of living things such as plants, animals, soil, water, air, sunlight and microorganisms. In the ecosystem, all these components depend on each other to maintain their survival. In civilization, population refers to a larger group and has certain characteristics that are to be studied and as a collection of individual organisms in a place that have similar characteristics, have the same origin. Based on the results of the implementation of learning in students with the results of student abilities after implementation, students were obtained classically above 96.77% with an average value of 78.19. Based on the results of the study, it can be concluded that the Lembak ethnic folklore has environmental civilization values that can be implemented in literature learning in junior high schools